2000
DOI: 10.1074/jbc.m005411200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Transcription of the Human Presenilin-1 Gene by Ets Transcription Factors and the p53 Protooncogene

Abstract: The expression of the human presenilin-1 cellular gene is suppressed by the p53 protooncogene. The rapid kinetic of the down-regulation has suggested that it may result from a primary mechanism. We show here that p53 also suppresses the transcription of a presenilin-1 promoter-chloramphenicol acetyltransferase reporter synthetic gene in transient infection assays in neuroblastoma (SK-N-SH) and hepatoma (HepG2) cell lines. Only a minimum promoter including sequences from ؊35 to ؉ 6 from the transcription initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 47 publications
4
62
0
Order By: Relevance
“…Moreover, Notch1 is cleaved by presenilin1, a component of g-secretase, and this generated NIC moves into the nucleus to form a transcriptional complex (Lai, 2002). p53 has been shown to downregulate presenilin-1 transcription and thereby inactivate thymic Notch1 signal (Roperch et al, 1998;Amson et al, 2000;Pastorcic and Das, 2000). The extreme elevation of NIC levels in the Pin1À/Àp53À/À thymocytes in the present study may have been caused in part by an increase in presenilin-1, as shown in Figure 4a.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Moreover, Notch1 is cleaved by presenilin1, a component of g-secretase, and this generated NIC moves into the nucleus to form a transcriptional complex (Lai, 2002). p53 has been shown to downregulate presenilin-1 transcription and thereby inactivate thymic Notch1 signal (Roperch et al, 1998;Amson et al, 2000;Pastorcic and Das, 2000). The extreme elevation of NIC levels in the Pin1À/Àp53À/À thymocytes in the present study may have been caused in part by an increase in presenilin-1, as shown in Figure 4a.…”
Section: Discussionmentioning
confidence: 57%
“…p53 downregulates presenilin-1, a component of the g-secretase complex required to cleave and consequently activate Notch1. Thus, p53 may negatively regulate Notch1 activation (Roperch et al, 1998;Amson et al, 2000;Pastorcic and Das, 2000). Notch1 is expressed at varying levels in developing and mature T cells, from hematopoietic progenitors to peripheral lymphocytes .…”
Section: Introductionmentioning
confidence: 99%
“…The sequence-specific transactivators Ets-1 and NF-Y, implicated in the regulation of cancer-associated genes (reviewed by Pang et al, 1996;Gu et al, 1999;Gilliland, 2001;Oikawa, 2004), have emerged as important constituents of the mutp53 transcriptome. In contrast to wtp53 which by binding to Ets-1 inhibits its transcriptional activity (Pastorcic and Das, 2000;Gu et al, 2004), mutp53 proteins cooperate with Ets-1 and augment the transcription of cancerassociated genes by Ets-1 (Sampath et al, 2001; our own unpublished data). Similarly, the interaction of mutp53 proteins with the transcription factor NF-Y converts the 'normal' functional outcome of the NF-Y interaction with wtp53.…”
Section: Introductionmentioning
confidence: 72%
“…Although wtp53 inhibits Sp1-dependent activation, presumably by interfering with DNA binding by Sp1 (Bargonetti et al, 1997), mutp53 proteins cooperate with Sp1 and amplify its activating effects on transcription. Similarly, the physical association between wtp53 and Ets-1 is inhibitory to Ets-1 activity (Pastorcic and Das, 2000) whereas the mutp53/Ets-1 interaction potentiates Ets-1-mediated transcription (Sampath et al, 2001). A similar picture emerges with regard to NF-Y.…”
Section: Mutp53: Role Of Residual Wtp53 Activity?mentioning
confidence: 80%
“…It appears most likely that functional interactions of the wtp53 N-terminal domain with the basal transcriptional machinery are also retained in mutp53 and are required for full transcriptional potency. Indeed, several of the proteins reported to interact with mutp53 and to affect its function are known to interact also with wtp53; these include Sp1 (Bargonetti et al, 1997;Pastorcic and Das, 2000;Kim and Deppert, 2003), Ets-1 (Sampath et al, 2001), and NF-Y (Di Agostino et al, 2006). Interestingly, the interactions of these proteins with wtp53 often result in opposite transcriptional outcomes than those observed with mutp53.…”
Section: Mutp53: Role Of Residual Wtp53 Activity?mentioning
confidence: 99%